Biological age estimation using DNA methylation analysis: A systematic review - Muhammad Garry Syahrizal Hanafi; Nurtami Soedarsono; Elza Ibrahim Auerkari (Wolters Kluwer Medknow Publications, 2021)
Age estimation is a fundamental part in forensic, criminal, legal, and anthropological investigations. The biomolecular analysis is considered to have a good capability in estimating age because it can describe a person's biological age. According to previous studies, DNA methylation has the best effectiveness for estimating biological age, compared to other biomolecular analysis. Although DNA methylation is influenced by a number of factors such as heredity, environment, lifestyle and systemic diseases, DNA methylation still has accuracy that accountable to estimate age. A literature review search of PubMed, ScienceDirect, Scopus, and EBSCO was conducted to get all studies that published before February 2020. The review was then performed on 22 papers that selected based on inclusion and exclusion criteria. The purpose of this reviewed paper was to identify all gene markers that have been used to estimate age using DNA methylation analysis; and to find out the subject, age range, tissue taken for DNA methylation analysis, and the effectiveness of the analysis.